2012
DOI: 10.1016/j.chb.2011.11.021
|View full text |Cite
|
Sign up to set email alerts
|

The role of perceived organizational support, distributive justice and motivation in reactions to new information technology

Abstract: Despite tremendous investments in information technology (IT), many technological interventions in organizations fail because employees do not fully accept and use IT. The present study explored how two aspects of work climateperceived organizational support and distributive justiceaffect employee reactions to new IT (i.e., usage and attitudes) from a motivational point of view. Self-determination theory was used to understand how different motivational styles, varying in degree of selfdetermination, mediate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 77 publications
2
86
0
7
Order By: Relevance
“…Justice and fairness have been extensively studied in various fields [85][86][87][88]. In tourism, studies on justice have focused on human resource management [89], revenue management [82,90], and customer service [91].…”
Section: Distributive Justicementioning
confidence: 99%
See 1 more Smart Citation
“…Justice and fairness have been extensively studied in various fields [85][86][87][88]. In tourism, studies on justice have focused on human resource management [89], revenue management [82,90], and customer service [91].…”
Section: Distributive Justicementioning
confidence: 99%
“…Thus, it is now considered a decision factor for technology adoption [86]. For a gamified mobile application, customers compare their expected experience using the application against the time and effort required by the application.…”
Section: Distributive Justicementioning
confidence: 99%
“…The method can be re-tested by measuring the variables included in the research through methods other than self-report. The importance of school culture in technology integration has been emphasised by many researchers (Ertmer, 1999;Mitchell, Gagné, Beaudry, & Dyer, 2012). In the present study, "technical support" was examined as one of the variables that can be considered as the reflection of school culture.…”
mentioning
confidence: 99%
“…In addition, none of these studies has accepted all the four motivation types of selfdetermination theory at the same time. Furthermore, a number of studies that adopt self-determination theory concluded that controlled motivation is not as much important as autonomous motivation when linked to knowledge sharing behaviors [11,[17][18]. Therefore, this study will only concentrate on autonomous motivations in SDT and conclude the quality of motivations presented in selfdetermination theory.…”
Section: A Self-determination Viewpoint On Knowledge Sharing Behaviormentioning
confidence: 99%